Билимлендириўдиң үзликсизлигин тәмийинлеў – тәлим-тәрбияның беккем таянышы - Шразов, М (SCIENCE and SOCIETY, 2021)
The article discusses the importance of the 11-year education system in the secondary schools of country. It is said that in the process of continuing education, the teaching of school-age children is much improved. Tálim - tárbiya teoriyası hám metodikası
Keywords: prevention; college; lyceum; guardianship; teenager; education